A Historical Biographical Analysis in The Novel Norwegian Wood by Haruki Murakami. - Laurie Binardi Wijaya (JELT: Journal of English Language Teaching, 2021)
Literature represents the culture and tradition of a language or a people. The word literature suggests a higher art form or merely putting the words on a page doesn’t necessarily equate to creating a literature. Even, the concept is difficult to precisely define. It’s clear to accepted definition of literature is constantly changing. According to Wellek and Warren (1963) says that “also state that the term literature seems best if we limit it to the art of literature, that is, to imaginative literature. Literature is also produced by imagination of the author. Literature is not just a document of facts, It is not just a collection of real events though it may happen in the real life. Literature can create its own world as product of unlimited imagination. Literature includes literary works such as novel, stories, poems, and plays composed in English in the study of English.